Lymphotoxin-α (LTα) Supports Development of Splenic Follicular Structure That Is Required for IgG Responses - Fu, Yang-Xin (The Rockefeller University Press, 1997)
LTα-deficient (LTα(−/−)) mice show altered splenic microarchitecture. This includes loss of normal B cell–T cell compartmentalization, of follicular dendritic cell (FDC) clusters, and of ability to form germinal centers (GC). LTα(−/−) mice immunized with sheep red blood cells (SRBC) produced high levels of antigen-specific IgM but no IgG in either primary or secondary responses, demonstrating failure of Ig class switching. This inability to switch to IgG could have been due to the altered splenic microarchitecture in these mice. Alternatively, it could have been due directly to a requirement for LTα expression by lymphocytes cooperating in the antibody response. To investigate this, we performed reciprocal spleen cell transfers. When irradiated LTα(−/−) mice were reconstituted with wild-type splenocytes and immunized immediately with SRBC, splenic microarchitecture remained disturbed and there was no IgG response. In contrast, when irradiated wild-type animals received splenocytes from LTα(−/−) mice, follicle structure and a strong IgG response were retained. These data indicate that LTα-deficient B cells and T cells have no intrinsic defect in ability to generate an IgG response. Rather, the altered microenvironment characteristic of LTα(−/−) mice appears to result in impaired ability to switch to a productive IgG response. To investigate whether prolonged expression of LTα could alter the structure and function of spleen follicles, reciprocal bone marrow (BM) transplantation was performed. Six weeks after reconstitution of LTα(−/−) mice with wild-type BM, spleen follicle structure was partially restored, with return of FDC clusters and GC. B cell/T cell compartmentalization remained abnormal and white pulp zones were small. This was accompanied by restoration of IgG response to SRBC. Reconstitution of wild-type mice with LTα(−/−) BM resulted in loss of FDC clusters and GC, and loss of the IgG response, although compartmentalized B cell and T cell zones were largely retained. Thus, defective IgG production is not absolutely associated with abnormal B cell and T cell compartmentalization. Rather, expression of LTα supports the maturation of spleen follicle structure, including the development and maintenance of FDC clusters, which supports Ig class switching and an effective IgG response.